2015
DOI: 10.1590/1519-6984.13812
|View full text |Cite
|
Sign up to set email alerts
|

Priming and temperature limits for germination of dispersal units of Urochloa brizantha (Stapf) Webster cv. basilisk

Abstract: The objective of this study was to evaluate the effect of priming treatments on the upper and lower thermal limits for germination of Urochloa brizantha cv. basilisk, and testing the hypothesis that pré-imbibition affect thermal parameters of the germination. Pre-imbibed seeds both in distilled water (0 MPa) and PEG 6000 solution (-0.5 MPa) were put to germinate in different temperatures. It is suggested that U. brizantha seeds have low response to priming when they were placed to germinate in medium where wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
3
0
1
Order By: Relevance
“…Similar results showed that Urochloa sp. (Poaceae) primed seeds had their optimum temperature changed to higher temperatures and that effect of priming was more intense at non-optimum temperatures, widening its germination temperature range (Nakao and Cardoso, 2015). In addition, the authors observed that there is generally a higher increase in T c than decrease in T b which may explain the increase in optimal and ceiling temperatures of the species in this study occurring in the Caatinga ecosystem, naturally characterized by high temperatures.…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…Similar results showed that Urochloa sp. (Poaceae) primed seeds had their optimum temperature changed to higher temperatures and that effect of priming was more intense at non-optimum temperatures, widening its germination temperature range (Nakao and Cardoso, 2015). In addition, the authors observed that there is generally a higher increase in T c than decrease in T b which may explain the increase in optimal and ceiling temperatures of the species in this study occurring in the Caatinga ecosystem, naturally characterized by high temperatures.…”
Section: Resultsmentioning
confidence: 53%
“…Seeking to predict the germinative behavior of some species, researchers have resorted to experiments by using controlled conditions and models based on population parameters, such as degree-days (thermal time), which allows estimating the time required for seed germination in a given thermal regime based on germinative parameters (Cardoso, 2011;Nakao and Cardoso, 2015). Such models allow quantifying the germinative response amid temperature changes in the environment.…”
Section: Introductionmentioning
confidence: 99%
“…ha −1 there was no significant difference (Table 2). This occurred because the greater volume of straw reduces average daily soil temperature [37] and exposure to light, which are the main regulators of seed germination [38][39][40][41]. The unavailability of light also causes the emergence of abnormal grass seedlings, with the development of only the aerial or root part, which limits photosynthesis and nutrient absorption, leading to the death of the seedlings [42].…”
Section: Resultsmentioning
confidence: 99%
“…Các stress nhẹ hay nhanh trước có thể giúp thực vật đáp ứng mạnh hơn hay kéo dài hơn với stress khác sau đó. Nghiên cứu ở Urochloa brizantha cho thấy việc tiền xử lý hột ở 40 ℃ giúp gia tăng khả năng nẩy mầm và tăng trưởng của cây trong điều kiện hạn [4]. Do đó, trong nghiên cứu này, chúng tôi tập trung tìm hiểu ảnh hưởng của tiền xử lý hột với nhiệt lên các biến đổi hình thái, sinh lý và sinh hóa trong quá trình tăng trưởng của cây cà chua trong điều kiện hạn nhằm gia tăng khả năng chịu hạn của cây cà chua.…”
Section: Science and Technology Development Journal Natural Sciencesunclassified